Neural stem/progenitor cells as promising candidates for regenerative therapy of the central nervous system - Bonnamain, Virginie; Neveu, Isabelle; Naveilhan, Philippe (Frontiers in Cellular Neuroscience, 2012)
Neural transplantation is a promising therapeutic strategy for neurodegenerative diseases and other affections of the central nervous system (CNS) like Parkinson and Huntington diseases, multiple sclerosis or stroke. If cell replacement therapy already went through clinical trials for some of these diseases using fetal human neuroblasts, several important limitations led to the search for alternative cell sources that would be more suitable for intracerebral transplantation. Taking into account logistical and ethical issues linked to the use of tissue derived from human fetuses, and the immunologically special status of the CNS allowing the occurrence of deleterious immune reactions, Neural Stem/Progenitor Cells (NSPCs) appear as an interesting cell source candidate. In addition to their ability for replacing cell populations lost during the pathological events, NSPCs also display surprising therapeutic effects of neuroprotection and immunomodulation. A better knowledge of the mechanisms involved in these specific characteristics will hopefully lead in the future to a successful use of NSPCs in regenerative medicine for CNS affections.